Occurrence and Genomic Characterization of ESBL-Producing, MCR-1-Harboring Escherichia coli in Farming Soil - Zheng, Beiwen; Huang, Chen; Xu, Hao; Guo, Lihua; Zhang, Jing; Wang, Xin; Jiang, Xiawei; Yu, Xiao; Jin, Linfeng; Li, Xuewen; Feng, Youjun; Xiao, Yonghong; et al. (Frontiers in Microbiology, 2017)
The emergence and spread of the mobile colistin resistance gene (mcr-1) has become a major global public health concern. So far, this gene has been widely detected in food animals, pets, food, and humans. However, there is little information on the contamination of mcr-1-containing bacteria in farming soils. In August 2016, a survey of ESBL-producing E. coli isolated from farming soils was conducted in Shandong Province, China. We observed colistin resistance in 12 of 53 (22.6%) ESBL-producing Enterobacteriaceae isolates from farming soil. Six mcr-1-positive E. coli strains originating from a livestock-intensive area were found. The isolates belonged to four different STs (ST2060, ST3014, ST6756, and ST1560) and harbored extensive additional resistance genes. An E. coli with blaNDM-1 was also detected in a soil sample from the same area. Comparative whole genome sequencing and S1-PFGE analysis indicated that mcr-1 was chromosomally encoded in four isolates and located on IncHI2 plasmids in two isolates. To our knowledge, we report the first isolation of mcr-1 in ESBL-producing E. coli from farming soils. This work highlights the importance of active surveillance of colistin-resistant organisms in soil. Moreover, investigations addressing the influence of animal manure application on the transmission of mcr-1-producing bacteria are also warranted.